Irradiation tests of photodiodes for the ATLAS SCT readout - Dowell, J; Homer, R; Kenyon, I; Mahout, G; Oglesby, S; Shaylor, H; Wilson, J; Nickerson, R; Wastie, R; Weidberg, A (Elsevier, 1999)
Two kinds of photodiodes have been investigated for the ATLAS SCT readout. We present in this paper the results of irradiating bulk and epitaxial Si PIN diodes with 1 MeV-equivalent neutrons and 24 GeV protons. The devices were biased during some of the tests. They were exposed to a fluence of around 2.5×10 14 n cm -2 followed by a fluence of approximately 2.5×10 14 p cm -2.